2000
DOI: 10.1007/s00223001102
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Directly Inhibits Bone-Resorbing Activity of Isolated Mature Osteoclasts Mainly Through the EP4 Receptor

Abstract: Prostaglandins (PGs) are well known to be important local factors in regulating bone formation and resorption. PGE2 is a potent stimulator of bone resorption because of enhancing osteoclast formation by its indirect action through stromal cells. However, the direct action of PGE2 on functionally mature osteoclasts is still controversial. In this study using highly purified rabbit mature osteoclasts, we examined the direct effect of PGE2 on osteoclastic bone-resorbing activity and its mechanism. PGE2 inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 44 publications
2
40
1
Order By: Relevance
“…Osteoclasts have also been shown to express EP4 abundantly (Mano et al, 2000). Although there are convincing in vitro and in vivo collective data indicating that EP2 receptors may have a role in PGE 2 -mediated RANKL expression and anabolic effects on bone, to date no functional EP2 receptors have been identified on human osteoblasts or osteoclasts (Akhter et al, 2001;Woodward et al, 2011).…”
Section: Other Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts have also been shown to express EP4 abundantly (Mano et al, 2000). Although there are convincing in vitro and in vivo collective data indicating that EP2 receptors may have a role in PGE 2 -mediated RANKL expression and anabolic effects on bone, to date no functional EP2 receptors have been identified on human osteoblasts or osteoclasts (Akhter et al, 2001;Woodward et al, 2011).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…The major effect of PGE 2 on resorption is generally considered to occur indirectly via upregulation of RANKL expression and by inhibition of osteoprotegrin expression in osteoblastic cells (Blackwell et al, 2010). It has been suggested that PGE 2 enhances osteoclast formation through EP4 receptor activation on osteoblasts (Mano et al, 2000;Sakuma et al, 2000). Osteoclast formation was enhanced by the presence of an EP4 agonist in coculture of mouse primary osteoblastic cells and bone marrow cells, but not in cocultures of primary osteoblastic cells from EP4 KO mice (Sakuma et al, 2000).…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…(2) 12-O-tetradecanoyl phorbol-13-acetate (TPA), an activator of PKC, decreased osteoclastic bone-resorbing activity. (3) A synthetic peptide fragment, PKC(530-558), which activates PKC, significantly inhibits osteoclastic bone resorption, and this effect is abolished in the presence of a synthetic peptide fragment PKC (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), which inhibits PKC, suggesting an important physiological role for the PKC pathway in osteoclast function. (4) In addition, synthetic diacylglycerols, analogs of the physiological activators of PKC, also inhibited bone resorption, providing further evidence for an important role of the PKC pathway in the regulation of osteoclast activity.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Moreover, PGE 2 can inhibit bone resorption by a direct action on mature osteoclasts. (11) In osteoblasts, PGE 2 , PTH, and mechanical loading stimulate an increase in intracellular calcium, likely via the production of inositol triphosphate, diacylglycerol, and cyclic adenosine monophosphate (cAMP). (12)(13)(14) This increase in intracellular Ca 2ϩ has been shown to trigger the opening of Ca 2 -dependent K ϩ channels of high conductance (BK).…”
Section: Introductionmentioning
confidence: 99%